2016
DOI: 10.21608/zvjz.2016.7881
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Some Immunostimulants on the Immune-response of Broiler Chickens Against Avian Influenza and Newcastle Diseases Vaccination

Abstract: Immunostimulants get an increasing importance to enhance the immune system and allowing maximum performance in poultry production. The effects of using different immunostimulants on the immune response of broiler chickens to Newcastle disease (ND) and Avian influenza (AI) vaccination were investigated in this study. 100 day-old Ross broiler chicks were randomly divided into 4 groups, 25 birds for each group. Group A was not treated with any immunostimulants and used as a control, while groups B, C and D were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although there are no reported cases of the corona virus transfer to chickens, optimizing the immune status of the birds in the farm is also a major priority to keep the health of the flocks at optimum to face any other outbreaks and infectious agents. This includes execution of a strict health program to avoid occurrence of viruses such as avian influenza or any other respiratory avian diseases (15,16). The elements of a good health program are good vaccination, disinfecting, cleaning, continuous monitoring, and pest control (1).…”
Section: Key Challenges To the Local Poultry Industry During The Covimentioning
confidence: 99%
“…Although there are no reported cases of the corona virus transfer to chickens, optimizing the immune status of the birds in the farm is also a major priority to keep the health of the flocks at optimum to face any other outbreaks and infectious agents. This includes execution of a strict health program to avoid occurrence of viruses such as avian influenza or any other respiratory avian diseases (15,16). The elements of a good health program are good vaccination, disinfecting, cleaning, continuous monitoring, and pest control (1).…”
Section: Key Challenges To the Local Poultry Industry During The Covimentioning
confidence: 99%
“…Several natural agents as an alternative to AGPs in poultry production were proposed, including phytogenic feed additives, enzymes, probiotics, prebiotics, synbiotics, organic acids, antibodies, bacteriophages, antimicrobial peptides and immunostimulants (Mehdi et al, 2018). The immunomodulators are any biologic or synthetic substances that stimulate (induction or activation) or suppress (inhibition) both the innate and adaptive immune responses (Abdel‐Hafez & Mohamed, 2016; Wils‐Plotz & Klasing, 2017). A number of researches showed that the natural lactoferrin (LF) has immunomodulatory properties (Adlerova et al, 2008; Blais et al, 2014; Geier et al, 2011; Lönnerdal, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several types of stimulants with different mechanisms and functions. Complex carbohydrates Apsa Mos ® is a wall extract with a high content (6).…”
Section: Introductionmentioning
confidence: 99%